Molecular orientation within thin films of isomorphic molecular semiconductors. Issue 108 (20th October 2015) - Liu, Xiaofeng; Burgers, Mark A.; Hsu, Ben B. Y.; Coughlin, Jessica E.; Perez, Louis A.; Heeger, Alan J.; Bazan, Guillermo C.
Abstract : Subtle structural variation of isomorphic molecular semiconductors leads to sharp contrast in electronic structures and molecular orientation in the bulk. Abstract : Four isomorphic organic semiconductors are compared to map out how the precision of chemical structures determines solid state molecular organization. Intramolecular electronic structure and intermolecular packing preference in the solid state were shown to be exclusively dependent on the relative location of the electron accepting fragments within a given molecule.